Common processes at unique volcanoes—a volcanological conundrum - Cashman, Katharine; Biggs, Juliet (Frontiers in Earth Science, 2014)
An emerging challenge in modern volcanology is the apparent contradiction between the perception that every volcano is unique, and classification systems based on commonalities among volcano morphology and eruptive style. On the one hand, detailed studies of individual volcanoes show that a single volcano often exhibits similar patterns of behaviour over multiple eruptive episodes; this observation has led to the idea that each volcano has its own distinctive pattern of behaviour (or “personality”). In contrast, volcano classification schemes define eruption “styles” referenced to “type” volcanoes (e.g. Plinian, Strombolian, Vulcanian); this approach implicitly assumes that common processes underpin volcanic activity and can be used to predict the nature, extent and ensuing hazards of individual volcanoes. Actual volcanic eruptions, however, often include multiple styles, and type volcanoes may experience atypical eruptions (e.g., violent explosive eruptions of Kilauea, Hawaii1). The volcanological community is thus left with a fundamental conundrum that pits the uniqueness of individual volcanic systems against generalization of common processes. Addressing this challenge represents a major challenge to volcano research.